KORELASI KONSENTRASI IAA DAN BAP TERHADAP PERTUMBUHAN KULTUR JARINGAN SENGON (Paraserianthes falcataria) - Nurhanis, Stefani Eka; Wulandari, Reine Suci; Suryantini, Rosa (JURNAL HUTAN LESTARI, 2019)
Sengon (Paraserianthes falcataria) is a fast growing plant that has high economic value. But the presence of sengon in the wild every year begins to decline due to the high demand for sengon wood. To increase the availability of sengon seeds, the propagation is carried out through tissue culture techniques. This study aims to determine the correlation between growth regulators (IAA and BAP) and the growth of sengon explants. This study used an experimental method with treatment of IAA concentrations of 0 mg/L, 0,5 mg/L, 1 mg/L, 1,5 mg/L, and 2 mg/L and BAP concentrations of 0 mg/L, 1 mg/L, 2 mg/L, 3 mg/L and 4 mg/L. Each treatment was repeated three times and analyzed using a simple correlation test analysis. The results showed, that the higher concentration of IAA and BAP, causes decreased growth of sengon explants, so the concentration of IAA and BAP gives a negative correlation, but provides a strong relationship to the percentage days of appearance of roots, shoots and leaves, plantlet height, root length, and number of leaves.Keywords : Correlation, plant tissue isolation method, sengon.